General practitioners' accounts of how to facilitate consultations with toddlers – an interview study. (2nd January 2017) - Golsäter, Marie; Johansson, Lars-Olof; Harder, Maria
Abstract: Objective: To describe general practitioners' (GPs') accounts of how to facilitate consultations with children aged 1–2 years. Design: A qualitative study based on focus group interviews. Setting and subjects: Five focus group interviews were conducted with a total of 25 GPs at Swedish primary health care (PHC) centres. The GPs regularly invited toddlers to consultations. Result: The GPs' accounts of how to facilitate consultations with toddlers revealed descriptions of making efforts to instil confidence in the situation to enable the consultation . Toddlers in need of health care always visit the GP with adults such as their parents, guardians or other relatives. Therefore, the GP directs efforts towards the adults and the child more or less simultaneously, as they both need to rely on the GP. The GPs describe how they instil confidence in the adults by establishing a mutual understanding that the consultation is necessary to secure the child's health. Regarding the child, the GP instils confidence by establishing a relationship in order to approach the child and accomplish bodily examinations. Conclusion: The result shows that GPs' encounters with children in consultations are two-sided. The GP needs to conduct bodily examinations to secure the child's health and development, but to do so he/she needs to establish purposeful relationships with the adults and the child by instilling confidence. This indicates that establishing relationships in the consultation is significant, and a way to achieve a child-centred consultation. KEY POINTS: Research regarding GPs' encounters with toddlers in consultation is limited, even though toddlers frequently visit PHC.  GPs make efforts to instil confidence by establishing mutual understanding with parents and a relationship with the child.  Establishing purposeful relationships with both the child and parent is significant in enabling the consultation.  Establishing a relationship with the child overrides conducting the bodily examination, to promote the child's feeling of ease and allow a child-centred consultation.